Use of English versus direct method in the teaching of Chinese vocabulary : a comparative study - Tan, Sing Hwa. (2009)
This study was an explorative rather than a hypothesis-testing research. The purpose of this study was to explore the effects of two different teaching methods, the direct method and the English method, in the teaching of Chinese vocabulary. It is an attempt to help students who are weak in Chinese language due to a lack of environment in learning Chinese to evoke more interest and prompt learning of Chinese vocabulary.